A place to land: spatiotemporal drivers of stopover habitat use by migrating birds. (7th October 2020) - Cohen, Emily B.; Horton, Kyle G.; Marra, Peter P.; Clipp, Hannah L.; Farnsworth, Andrew; Smolinsky, Jaclyn A.; Sheldon, Daniel; Buler, Jeffrey J.
Abstract: Migrating birds require en route habitats to rest and refuel. Yet, habitat use has never been integrated with passage to understand the factors that determine where and when birds stopover during spring and autumn migration. Here, we introduce the stopover‐to‐passage ratio (SPR), the percentage of passage migrants that stop in an area, and use 8 years of data from 12 weather surveillance radars to estimate over 50% SPR during spring and autumn through the Gulf of Mexico and Atlantic coasts of the south‐eastern US, the most prominent corridor for North America's migratory birds. During stopovers, birds concentrated close to the coast during spring and inland in forested landscapes during autumn, suggesting seasonal differences in habitat function and highlighting the vital role of stopover habitats in sustaining migratory communities. Beyond advancing understanding of migration ecology, SPR will facilitate conservation through identification of sites that are disproportionally selected for stopover by migrating birds. Abstract : Using 8 years of data from 12 weather surveillance radars, we found over 50% of the birds migrating through the south‐eastern US coastlines stop there, totalling c . 1.2 to 2.0 billion birds each spring and autumn. The drivers of stopover habitat use differed between spring and autumn migration, suggesting seasonal differences in habitat function. Furthermore, disparities in disproportionate selection and absolute abundance at stopover sites revealed potential migratory bottlenecks where geography or restricted habitat may disproportionately concentrate birds along migration routes, highlighting that density of use alone is not a comprehensive measure of the conservation value of a stopover site for migrating birds, a topic that has not been addressed during migration. The question of where and when migrating communities stop en masse relative to passage rates, and within and between seasons, remains an open question for migration systems globally.